Editoriale/Editorial/Éditorial/Editorial (Altre Modernità, 2019)
Mind the gap in tourism discourse: translation, mediation, inclusion by Mirella Agorni and Cinzia Spinzi  Mirella Agorni wrote the first part of this introduction (up to the reference to Bailini’s article), whereas Cinzia Spinzi wrote the second part of the introduction (from the reference to Tonin’s article to the end)